2007
DOI: 10.1029/2006jf000729
|View full text |Cite
|
Sign up to set email alerts
|

Relation between rock uplift and denudation from cosmogenic nuclides in river sediment in the Central Alps of Switzerland

Abstract: [1] A north-south traverse through the Swiss Central Alps reveals that denudation rates correlate with recent rock uplift rates in both magnitude and spatial distribution. This result emerges from a study of in situ-produced cosmogenic 10 Be in riverborne quartz in Central Alpine catchments. As a prerequisite, we took care to investigate the potential influence of shielding from cosmic rays due to snow, glaciers, and topographic obstructions; to calculate a possible memory from Last Glacial Maximum (LGM) gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
287
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 210 publications
(313 citation statements)
references
References 82 publications
26
287
0
Order By: Relevance
“…It is important to note here that the use of suspension load measurements over a short time period can often result in substantial underestimates of sediment transfer (e.g., Kirchner et al, 2001;Schaller et al, 2001). Wittmann et al (2007) observed such underestimates for the Central Alps by comparing river loads with cosmogenic nuclide-derived denudation rates (figs 2B and 2C). Underestimates possibly arose because of the lack of inclusion of solute and bedload transport, sediment trapping by retention dams, or because the time span during which suspended load concentrations have been measured is too short to sample the high-magnitude floods that are considered to be the most effective mechanisms for sediment discharge (Kirchner et al, 2001;Molnar, 2001;Dadson et al, 2003).…”
Section: Suspended Loadsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note here that the use of suspension load measurements over a short time period can often result in substantial underestimates of sediment transfer (e.g., Kirchner et al, 2001;Schaller et al, 2001). Wittmann et al (2007) observed such underestimates for the Central Alps by comparing river loads with cosmogenic nuclide-derived denudation rates (figs 2B and 2C). Underestimates possibly arose because of the lack of inclusion of solute and bedload transport, sediment trapping by retention dams, or because the time span during which suspended load concentrations have been measured is too short to sample the high-magnitude floods that are considered to be the most effective mechanisms for sediment discharge (Kirchner et al, 2001;Molnar, 2001;Dadson et al, 2003).…”
Section: Suspended Loadsmentioning
confidence: 99%
“…In a recent publication, Wittmann et al (2007) applied in situ-produced cosmogenic nuclides to estimate erosion rates for various catchments in the Central Swiss Alps. This method, using the concentration of Be in river sediment 10…”
Section: Denudation Rates From Cosmogenic 10mentioning
confidence: 99%
See 3 more Smart Citations